Flexor Digitorum Longus Transfer in Chronic Plantar Plate Tears: Two Case Reports and Literature Review - Antonio Córdoba-Fernández; Rocío Mateos-Carrasco; Antonio Jesús García-Gámez; Victoria Eugenia Córdoba-Jiménez (Reports)
Background and Clinical Significance: The plantar plate (PP) tear of the second metatarsophalangeal joint (MTPJ) is a common cause of forefoot pain in clinical practice. The PP is the main stabilizing structure of the joint and, together with the collateral ligaments, is the key to maintaining the stability of the MTPJ. Many surgical procedures have been described to repair PP tears. Currently, there is still controversy regarding which is the surgical superior option (direct versus indirect PP repair techniques). Transfer of the flexor digitorum longus tendon to the dorsum of the proximal phalanx is one of the surgical techniques described to treat PP tears associated with MTPJ instability. Case Presentation: We present two cases that developed instability of the second MTPJ secondary to chronic PP tear with symptoms resolved after transfer of the flexor digitorum longus (FDL). Conclusions: Currently, the literature review shows that the procedure seems to be the most consistent surgical option in chronic cases of PP tears.